Perturbations in the Ionosphere Following U. S. Powerful Space Vehicle Launching - Chernogor, L. F.; Garmash, K. P.; Kostrov, L. S.; Rozumenko, V. T.; Tyrnov, O. F.; Tsymbal, A. M. (Видавничий дім «Академперіодика», 2013)
Perturbations in the Ionosphere Following U. S. Powerful Space Vehicle Launching